Biotechnology for Wastewater Treatment from Textile Enterprises in the Bukhara Region - Hamroqulova, Xolliyeva Dilnavoz (American Journal of Biology and Natural Sciences, 2025)
Textile enterprises in the Bukhara region play an important role in the socio-economic development of the area; however their operations generate considerable volumes of wastewater containing toxic compounds. Conventional treatment methods often demonstrate limited efficiency and frequently fail to meet current environmental standards. Increasing attention has been directed toward the application of biotechnological methods for wastewater treatment. These include microbial treatment, enzymatic degradation of pollutants and bioaugmentation. Such approaches rely on the activity of biological systems to decompose organic and inorganic contaminants and are generally characterized by higher environmental sustainability compared to physicochemical techniques. Considering the industrial structure of the Bukhara region biotechnology-based methods show a promising direction for improving the efficiency of textile wastewater treatment. This study examines key biotechnological approaches evaluates their potential applicability to local conditions, and provides recommendations for their practical implementation.